Shrines of the slave trade : Diola religion and society in precolonial Senegambia - Baum, Robert M. (ACLS Humanities E-Book., 1999)
In this groundbreaking work, Robert Baum seeks to reconstruct the religious and social history of the Diola communities in southern Senegal during the precolonial era, when the Atlantic slave trade was at its height. Baum shows that Diola community leaders used a complex of religious shrines and priesthoods to regulate and contain the influence of the slave trade. He demonstrates how this close involvement with the traders significantly changed Diola religious life.